(untitled) (Journal of Asian Development Studies, 2025)
Maternal morbidity and mortality remain a serious challenge in low- and middle-income settings, often driven by delays in recognising and acting upon obstetric danger signs (ODS). In Sindh, Pakistan, data on pregnant women’s awareness of such signs are scarce. This cross-sectional study assessed the knowledge of twelve key ODS among 415 antenatal women (≥12 weeks’ gestation) attending Liaquat University Hospital in Jamshoro and Hyderabad. Knowledge was scored from 0 to 12 and classified as poor (0–4), average (5–8), or good (9–12). Results revealed that 46.3% of participants had poor knowledge, 39.0% had average knowledge, and only 14.7% achieved good knowledge of danger signs. Higher awareness was significantly associated with maternal education (p < 0.001), parity (p = 0.003), past obstetric complications (p = 0.021), and multiple ANC visits (p < 0.001). Alarmingly, 62.2% of women reported receiving no counselling during pregnancy; among those counselled, healthcare providers served as the source in 94.3% of cases. The findings highlight substantial gaps in women’s recognition of critical obstetric warning signs, especially among those with limited education and early in their ANC engagement. Intensified, structured counselling during prenatal visits and broader community-based maternal health education may help mitigate the "first delay" in seeking care, ultimately reducing preventable maternal deaths.